KESESUAIAN JENIS TANAH TERHADAP TANAMAN UNTUK MENINGKATKAN PRODUKTIVITAS BISNIS HASIL PERKEBUNAN DENGAN GEOPROCESSING - Haryo Kusumo; febryan tahanuji (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
Suitability to the plantation soil type is very important, because can increase the productivity of plantation crops. From the observation in Boyolali, there are several types of soil, includingregosol, Andosol, litosol, mediterranean, grumosol. Geographic Information Systems (GIS) is one of the appropriate steps to present the spatial aspect (spatial). SIG has benefits that can be used to analyze the suitability of land in accordance with predetermined parameters, the type of soil, crop types and data sub-district in Boyolali. This study aimed to analyze the suitability of the soil to increase the productivity of plantations in Boyolali using Geoprocessing techniques. Following the Geoprocessing techniques in all sub-districts boyolali, most soil types are regosol and mediterranean contained in 15 districts, so it can be concluded that the type of plants should be planted in the district is coffee, Kina, Cinnamon, Crops, Fruits.